Mempersiapkan Generasi Milenial Yang Andal Sebagai Pemimpin Bangsa - Faruq Hasan Asy’ari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The millennial generation is a generation born between 1980-2000 when there was rapid technological progress and continues to grow. They are called the millennial generation because they are the generation that lives at the turn of the millennium. Simultaneously in today's digital technology began to penetrate into human life rapidly. When viewed from the age, this millennial generation is between 21-41 years old. In this paper, data were obtained from articles and journals, books, and news sources in the mass media. This study uses descriptive analysis method to analyze the data. A leader is someone who is able to move others by commanding, directing, and guiding others, in order to take action in order to achieve an expected goal according to the agreement. With the development of the times, many leaders emerged because of the demands and environmental conditions at this time. Then in the growing era of the millennial generation, the government should have prepared what the millennial generation needs so that they will become ideal leaders for the Indonesian people. In order to be realized, the millennial generation as the regeneration of the nation's leaders must be prepared from an early age by providing nationalism, religion, character and moral education.